2000
DOI: 10.1002/(sici)1099-1115(200003/05)14:2/3<109::aid-acs588>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear sensorless indirect adaptive speed control of induction motor with unknown rotor resistance and load

Abstract: In this paper, a nonlinear indirect adaptive sensorless speed and flux tracking controller for induction motors is proposed. In the controller, only the stator currents are assumed to be measurable. Flux observers and rotor speed estimator are designed to relax the need to flux and speed measurement. Besides, two estimators are also designed to overcome drifting problem of the rotor resistance and unknown load torque. Rigorous stability analysis based on Lyapunov theory is also performed to guarantee that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In any case, if braking actions are not considered, every pair of constant reference signals * and * c >0 satisfies condition (17) so that closed-loop boundedness may be guaranteed for any motor parameters and any constant operating condition. The second result of the paper is stated in the following theorem, which provides sufficient conditions for the exponential stability of the equilibrium y = 0 of the closed-loop system (1) and (8)- (11).…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, if braking actions are not considered, every pair of constant reference signals * and * c >0 satisfies condition (17) so that closed-loop boundedness may be guaranteed for any motor parameters and any constant operating condition. The second result of the paper is stated in the following theorem, which provides sufficient conditions for the exponential stability of the equilibrium y = 0 of the closed-loop system (1) and (8)- (11).…”
Section: Remarkmentioning
confidence: 99%
“…Assuming that rotor speed and stator currents measurements are available for feedback, significant advances have been made on induction motor control [1][2][3][4][5]. Recent research efforts are focused on the speed-sensorless induction motor control, in which rotor speed measurements are not available for feedback: several approaches have been proposed and a large number of papers have been devoted to this problem [6][7][8][9][10][11][12][13][14][15][16][17]. In [17], a speed estimation method is proposed, which is incorporated in a field orientation control scheme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chiasson (1998), it is shown that the approach of Chiasson (1993), presented in the ( , ) a b frame is greatly simplified by considering the model in the ( , ) d q frame. In Lin, Fu, and Tsai (2000) a nonlinear indirect adaptive sensorless speed and flux tracking controller for induction motors is proposed. In the controller, only the stator currents are assumed to be measurable.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the research and development of some methods of PMACM control avoiding those sensors [5]. Other techniques have been proposed for different machines [2], [6], [7].…”
mentioning
confidence: 99%